Praying for Rain - Espín-Sánchez, José-Antonio; Gil-Guirado, Salvador; Ryan, Nicholas (Quarterly Journal of Economics, 2026)
Abstract We study rainmaking as an instrumental religious belief. We present a model in which a religious leader tries to persuade people to believe. Praying for rain can persuade only where the hazard of rainfall during a dry spell is increasing over time, so that prayer is most likely to succeed when people most want rain. We present evidence from prayers for rain in Murcia, Spain, where the hazard rate is increasing, that the church’s prayers for rain predict rainfall over two centuries. To generalize this finding, we gather an original data set of whether ethnic groups around the world traditionally prayed for rain. We find that ethnic groups facing an increasing rainfall hazard are 47% more likely to pray for rain, consistent with our model’s prediction that societies are more likely to pray for rain where prayer is persuasive.